Konsep Reward Dan Punishment Dalam Mendidik Anak Di Lingkungan Keluarga Menurut Ajaran Rasulullah SAW - Usman Usman (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This type of research is library research, that is, research and studies are carried out by tracing and examining literature or written sources related to the subject matter. The type of data in this study is qualitative data. Qualitative data, namely in the form of literature from various experts. Secondary data sources are data that come from literature books where all information is related to this problem. In analyzing the data obtained and as an attempt to draw conclusions, the collected data will be analyzed using a qualitative descriptive analysis. Based on the results of the analysis, this study produced several findings, namely that giving rewards does not always have to be expensive. But there is nothing wrong with giving children rewards in the form of goods. As long as the item is really needed. When a child makes a mistake, don't be scolded immediately, because this can cause the child to be psychologically depressed..